Cancer-testis antigen lactate dehydrogenase C4 as a novel biomarker of male infertility and cancer - Wu, Jing; Chen, Yan; Lin, Yingying; Lan, Fenghua; Cui, Zhaolei (Frontiers in Oncology, 2022)
A unique lactate dehydrogenase (LDH) isoenzyme designated as lactate dehydrogenase C4 (LDH-C4) is found in mammalian mature testis and spermatozoa. Thus far, LDH-C4 has been well studied with regard to its gene and amino acid sequences, structure, biological properties, and peptide synthesis. Accumulating evidence has shown that LDH-C4 is closely related to spermatic energy metabolism and plays a critical role in sperm motility, capacitation, and fertilization. Defects in the catalytic activity of LDH-C4 are key to pathophysiological abnormalities underlying infertility. LDH-C4 was originally thought to be present only in mature testis and spermatozoa; however, recent studies have implicated LDH-C4 as a cancer-testis antigen (CTA) owing to its aberrant transcription in a broad spectrum of human neoplasms. This review highlights the recent findings on LDH-C4 with particular emphasis on its role in male infertility and tumors.